Datos meteorológicos de la Estación Gonnet del LAyHS (FAU-UNLP) correspondientes al año 2010 - Czajkowski, Jorge Daniel (2011)
Datos meteorológicos de la Estación Gonnet del LAyHS (FAU-UNLP) correspondientes al año 2010.